Investigation of the dynamic evolution of the CO2 carrying capacity of solids with time in La Pereda 1.7 MWth calcium looping pilot plant. (January 2020) - Diego, M.E.; Arias, B.; Abanades, J.C.
Highlights: The evolution of sorbent activity is studied in a large Calcium Looping pilot plant. Sorbent activity changes rapidly after modifications in the operating conditions. Two residence time distribution models were developed to interpret the results. The modelling approaches successfully predict the evolution of sorbent activity. Abstract: Calcium Looping (CaL) is a technology that makes use of CaO to capture CO2 from industrial flue gas sources in a carbonator, after which the CO2 is released in a concentrated form in an oxyfired calciner. The CO2 carrying capacity of the particles circulating between the carbonator and calciner is a key variable, as it is intimately linked to CO2 capture efficiency in the carbonator reactor. Therefore, the ability to predict dynamic changes in the CO2 carrying capacity of the sorbent is required to understand the dynamic performance of CaL systems. This work investigates the dynamic evolution of the average CO2 carrying capacity of the sorbent (Xave ) during transient scenarios in a large CaL pilot plant. Several experimental campaigns with extensive solids sampling and analyses were carried out to analyse the evolution of Xave with time when the make-up flow fed into the calciner is modified (between 0–2.7 kmol CaCO3 /h). Variations in Xave were tracked and the observed trends were interpreted using two residence time distribution models of different complexity. The main characteristics and limitations of each model are discussed in this study. The choice between the two modelling approaches developed in this work depends on the input information available and the degree of accuracy required for each specific application.